Factors Affecting Knowledge Transfer in Project Environments - Ionel NĂFTĂNĂILĂ (Revista de Management Comparat International)
Most project teams consist of knowledge workers, and the issue of how to better transfer knowledge across individuals and groups becomes a central concern. The main purpose of this article is to study the factors affecting the knowledge transfer process and their importance for project’s success. The factors analyzed in this article are trust among individuals, members of the team, project culture, values and the beliefs of the individuals and motivation of those involved in the project, both intrinsic and extrinsic. In order to overcome the barriers affecting the knowledge transfer process, project managers must create an environment where knowledge workers must feel free to share and re-use their knowledge.